Dried blood spot sampling as an alternative for the improvement of hepatitis B and C diagnosis in key populations - Flores, Geane Lopes (World J Hepatol, 2021)
BACKGROUND: To achieve the elimination of hepatitis B and C, there is an urgent need to develop alternative strategies to increase the access of diagnosis, particularly among key populations such as people living with human immunodeficiency virus (HIV), individuals with coagulopathies and chronic kidney disease (CKD) patients. AIM: To evaluate the use of dried blood spot (DBS) in the detection of hepatitis B virus (HBV) and hepatitis C virus (HCV) markers. METHODS: A total of 430 individuals comprised of people living with HIV, coagulopathies and CKD provided paired serum and DBS samples. HBsAg, anti-HBc and anti-HCV were tested in those samples using a commercial electrochemiluminescence. Demographic and selected behavioral variables were evaluated to assess possible association with HBV and HCV positivity. RESULTS: Using DBS, HBsAg prevalence varied from 3.9% to 22.1%, anti-HBc rates varied from 25.5% to 45.6% and anti-HCV positivity ranged from 15.9% to 41.2% in key populations. Specificities of HBV and HCV tests using DBS varied from 88.9% to 100%. The HBsAg assay demonstrated the best performance in CKD and coagulopathy individuals and the anti-HCV test had a sensitivity and specificity of 100% in people living with HIV. Accuracy of HBV and HCV detection in DBS varied from 90.2% to 100%. In the CKD group, HBsAg positivity was associated with infrequent use of condoms, and anti-HBc positivity was associated with sharing nail cutters/razors/toothbrushes. Anti-HCV reactivity was positively associated with a history of transplantation and length of time using hemodialysis in both specimens. In people living with HIV, only the male gender was associated with anti-HBc positivity in serum and DBS. CONCLUSION: DBS with electrochemiluminescence are useful tools for the diagnosis and prevalence studies of hepatitis B and C among key populations and may increase the opportunity to foster prevention and treatment.